The Healthy Ageing Unit: A comparative controlled intervention - Michael, Rene; Wheeler, B.; Wichmann, Helen; Horner, Barbara; Downie, Jill (Australasian Rehabilitation Nurses Association, 2005)
This article describes the second stage of a three- stage pilot research project to establish and evaluate a Healthy Ageing Unit, in a private hospital in Western Australia, based on a multi-disciplinary model of transitional rehabilitation for the elderly acute patient. The objective of the second stage and thus this study was to compare clinical outcomes of patients admitted to the Unit to those on a conventional post-acute care ward. The clinical outcomes included length of stay, patient functional status, confidence and emotional state. One hundred and sixty-eight inpatients participated in the study. One hundred and thirty-five (80.4%) patients were transferred to the Unit and formed the intervention group and 33 (19.6%) patients receiving conventional care formed the control group. Results analysed using appropriate parametric and non-parametric statistics revealed that the Healthy Ageing Unit had a positive impact on the set of apnori determined patient outcomes. Moreover, the staffing model adopted, where enrolled nurses trained as therapy assistants provided the majority of care under the direction of clinical registered nurses, supported good use of beds and improved labour costs per patient day. In addition, the Healthy Ageing Unit was seen to raise the profile of care of the older person within the health care organisation, as well as providing staff with an opportunity to develop alternative nursing roles that were more closely aligned with the humanistic approach to practice.